Assessment of the durability of low-cost Al bipolar plates for High Temperature PEM fuel cells. (17th May 2019) - Alegre, Cinthia; Álvarez-Manuel, Laura; Mustata, Radu; Valiño, Luis; Lozano, Antonio; Barreras, Félix
Abstract: The present research aims to assess the durability of a single cell formed by a commercial high-temperature membrane electrode assembly (MEA) and Al bipolar plates (Al-BPPs) coated with Ni-P. To this end, an accelerated degradation test based on voltage load cycles is carried out, and the effects of the degradation on the MEA and its impact on the Al-coated bipolar plates are analyzed. They are compared with the results obtained testing a similar cell formed by the same MEA with graphite plates. MEAs from both cells were analyzed by different characterization techniques before and after the degradation tests (XRD, SEM, TEM). The performance of the Al-based cell is initially better, but it suffers a faster deterioration mainly due to the degradation of the Ni-P surface coating. A green deposit is formed, probably due to the chemical reaction of the phosphoric acid leached from the MEA. These deposits cause an increase in the contact resistance of the plates, local channel blockages and, eventually, a larger degradation. This work proves that PBI membranes still need to be improved to ensure their long-term durability. Highlights: Ni-P-coated Al bipolar plates are assessed for High Temperature PEM fuel cells. MEA degradation is induced by accelerated stress tests based on voltage load cycles. Graphite bipolar plates are also tested for the sake of comparison. Cell with Al-plates presented a better initial performance but a higher degradation. Acid leaching from the MEA is responsible for both MEA and Al-plates degradation.